2010
DOI: 10.1007/s10562-010-0499-5
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry in the Center for Catalytic Hydrocarbon Functionalization: An Energy Frontier Research Center

Abstract: Selective catalysts that activate small molecules such as hydrocarbons, dioxygen, water, carbon dioxide and dihydrogen are central to new technologies for the use of alternative energy sources. For example, controlled hydrocarbon functionalization can lead to high impact technologies, but such catalysts require a level of molecular control beyond current means. The Center for Catalytic Hydrocarbon Functionalization facilitates collaborations among research groups in catalysis, materials, electrochemistry, bioi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…This may be accounted for by the rapid over-oxidation of, in particular, H 2 CÀ(OH) 2 to HCOOH. However, it is also possible that H 2 CO and H 2 C(OH) 2 were not produced during the reaction. Indeed, evaluation of the stability of possible reaction products under our experimental conditions demonstrated that at least H 2 CO, if formed, should be detected during the reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be accounted for by the rapid over-oxidation of, in particular, H 2 CÀ(OH) 2 to HCOOH. However, it is also possible that H 2 CO and H 2 C(OH) 2 were not produced during the reaction. Indeed, evaluation of the stability of possible reaction products under our experimental conditions demonstrated that at least H 2 CO, if formed, should be detected during the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…[1] Methane, the major component of fossil resources such as natural gas and clathrate fields, is one such promising alternative feedstock. [2] In spite of its significant natural abundance and its relatively inexpensive commodity price, methane is still a hugely underutilised resource. Although methods of converting methane to value-added products and fuels are practiced industrially, [3] these are not economically viable in remote regions where a significant fraction of the worlds reserves are found.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Hydraulic fracturing supplies much of this earth-abundant source from shale,w hich make chemical and energy transformations economical. Thermodynamic calculations suggest that the reaction toward methanol production is highly favorable compared to formation of ab yproduct, methyl peroxide.…”
mentioning
confidence: 99%
“…

Direct conversion of methane to chemical feedstocks such as methanol under mild conditions is ac hallenging but ideal solution for utilization of methane.P d 1 O 4 single-sites anchored on the internal surface of micropores of am icroporous silicate exhibit high selectivity and activity in transforming CH 4 to CH 3 OH at 50-95 8 8Cinaqueous phase through partial oxidation of CH 4 with H 2 O 2 .T he selectivity for methanol production remains at 86.4 %, while the activity for methanol production at 95 8 8Ci sa bout 2.78 molecules per Pd 1 O 4 site per second when 2.0 wt %C uO is used as ac ocatalyst with the Pd 1 O 4 @ZSM-5. Thec onversion rate of CH 4 to CH 3 OH at as olid-liquid interface pioneered by Hutchings et al [4a,5] is typically higher than these at as olid-gas interface, [3a,b] though the rate is still relatively low.Although catalytic activity for direct oxidation of CH 4 to CH 3 OH on these catalysts at solid-gas and solid-liquid interfaces was reported, [1,[3][4][5][6] challenges remain before ad irect oxidation process under mild conditions could be considered as ap otential approach in the chemical industry. [1] Hydraulic fracturing supplies much of this earth-abundant source from shale,w hich make chemical and energy transformations economical.

…”
mentioning
confidence: 99%
See 1 more Smart Citation